Comparison between two derivatization methods of nitrite ion labeled with 15N applied to liquid chromatography-tandem mass spectrometry. Issue 31 (25th July 2018) - Haiyan, Yu; Romain, Schmitt; Anne, Sapin; Patrick, Chaimbault; Pierre, Leroy
Abstract : 15 N assisted-derivatization strategies to improve the limit of quantification of nitric oxide species. Abstract : The fragmentations of the adducts resulting from the derivatization of nitrite ion by Griess method (formation of an azo compound) and 2, 3-diaminonaphthalene (formation of 2, 3-naphthotriazole (NAT)) were studied by tandem mass spectrometry (MS/MS). The transition used for quantification was selected according to the highest value of the signal-over-blank ratio (S/B) obtained from each adduct fragmentation. When derivatizing nitrite ion labeled with the stable 15 N isotope, followed by liquid chromatography (LC)-MS/MS measurement, the lowest limit of quantification obtained was 5 nM with NAT. The method was applied to study the intestinal permeability of S -nitrosoglutathione, a drug candidate for the chronic treatment of cardiovascular disease. This compound was labeled with 15 N and its permeability was studied in an ex vivo rat intestine model using an Ussing chamber.